2022
DOI: 10.3389/ijph.2022.1604517
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception Related to COVID-19 and Future Affective Responses Among Healthcare Workers in Switzerland: A Mixed-Methods Longitudinal Study

Abstract: Objectives: Whereas early findings suggest that risk perceptions related to COVID-19 affect psychological well-being in healthcare workers (HCWs), the temporal associations between these variables need to be clarified and HCWs lived experience further explored. This study proposes a mixed evaluation of COVID-19-related risk perception and affective responses among HCWs.Methods: A longitudinal mixed-method study was conducted. HCWs (N = 138) completed measures of COVID-19 risk perceptions, depression, anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…When examining individual RP questions, their highest level of concern was related to the transmission of COVID-19 to family members, friends, and patients. Previous studies have also shown that healthcare workers were more concerned about infecting others, especially family members and loved ones, than about being infected themselves [ 33 , [51] , [52] , [53] ]. Therefore, the government and/or employing organization should provide healthcare workers with essential resources (e.g., masks and hand sanitizers) to protect their families or alternative housing arrangements to prevent transmission.…”
Section: Discussionmentioning
confidence: 99%
“…When examining individual RP questions, their highest level of concern was related to the transmission of COVID-19 to family members, friends, and patients. Previous studies have also shown that healthcare workers were more concerned about infecting others, especially family members and loved ones, than about being infected themselves [ 33 , [51] , [52] , [53] ]. Therefore, the government and/or employing organization should provide healthcare workers with essential resources (e.g., masks and hand sanitizers) to protect their families or alternative housing arrangements to prevent transmission.…”
Section: Discussionmentioning
confidence: 99%